2022
DOI: 10.1039/d2fo00839d
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol improves strenuous exercise-associated cardiac pathological changesviamodulation of mitochondrial homeostasis

Abstract: Hydroxytyrosol (HT) from olive oil exerts profitable effects on strenuous exercise-induced cardiac pathological changes via modulation of mitochondrial homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…No genotoxicity of HT has been reported in humans, and multiple benefits have been revealed in the past decades through extensive studies [36]. We previously reported that HT could prevent diet-induced metabolic syndrome [37] and improve strenuous exercise-associated cardiac pathological changes [38] as well as protecting RPE cells against oxidative stress via activating Nrf2 signaling [17]. Other phenol compounds such as tyrosol and oleuropein have also been reported to activate Nrf2 for the protection of cellular stress and damage [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…No genotoxicity of HT has been reported in humans, and multiple benefits have been revealed in the past decades through extensive studies [36]. We previously reported that HT could prevent diet-induced metabolic syndrome [37] and improve strenuous exercise-associated cardiac pathological changes [38] as well as protecting RPE cells against oxidative stress via activating Nrf2 signaling [17]. Other phenol compounds such as tyrosol and oleuropein have also been reported to activate Nrf2 for the protection of cellular stress and damage [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…EE decreases the number of myocardial mitochondria and the mass of the myocardium by downregulating Mfn2 and increasing Drp1, resulting in energy metabolism imbalance and myocardial damage. In addition, the expression of Mfn1 and OPA1 was not affected by EE (37,54). Another study illustrated that phosphorylation of Drp1, but not Drp1, affects mitochondrial fission during EE.…”
Section: Figurementioning
confidence: 98%
“…Knockdown of PGC-1α may cause stalled mitochondrial turnover and death in cardiomyocytes, thereby affecting cardiac function and leading to a reduction in exercise-induced metabolic benefits (36). EE leads to a marked downregulation of PGC-1α and mitochondrial respiratory chain complexes I and II in the heart, along with a reduction in mtDNA copy number (37). A drop in mitochondrial complex I and II activity would suppress mitochondrial oxidative phosphorylation and increase ROS yield.…”
Section: Role Of Mitochondrial Biogenesis In Ee-induced Myocardial In...mentioning
confidence: 99%